Central and peripheral neurotoxicity induced by the Jack Bean Urease (JBU) in Nauphoeta cinerea cockroaches. (10th August 2016) - Carrazoni, Thiago; de Avila Heberle, Marines; Perin, Ana Paula Artusi; Zanatta, Ana Paula; Rodrigues, Polyana Veloso; dos Santos, Fabiola Duarte Machado; de Almeida, Carlos Gabriel Moreira; Vaz Breda, Ricardo; dos Santos, Douglas Silva; Pinto, Paulo Marcos; da Costa, Jaderson Costa; Carlini, Celia Regina; et al.
Highlights: Jack Bean Urease (JBU) alters behavior and physiology in Nauphoeta cinerea . JBU induced a positive cardiac chronotropic effect in N. cinerea . The cardiac effects of JBU rely on the insect cholinergic system. JBU increased leg but not antennae grooming by an octopaminergic route. JBU induces in vivo irreversible blockade of the coxal-adutor muscle in cockroaches. Abstract: Background: Ureases of Canavalia ensiformis are natural insecticides with a still elusive entomotoxic mode of action. We have investigated the mechanisms involved in the neurotoxicity induced by Jack Bean Urease (JBU) in Nauphoeta cinerea (Olivier). Methods: To carry out this study we have employed biochemical and neurophysiological analysis of different cockroach organ systems. Results and conclusions: The injection of the insects with JBU (0.75–6 μg/g animal), although not lethal within 24 h, caused significant inhibition of the brain acetylcholinesterase activity (60 ± 5%, p < 0.05, n = 6). JBU (1.5 μg/200 μL), acetylcholine (0.3 μg/200 μL) or neostigmine (0.22 μg/200 μL), induced a positive cardiac chronotropism (∼25%) in the cockroaches ( p < 0.05, n = 9). JBU (6 μg/g) increased the insects' grooming activity (137 ± 7%), similarly to octopamine (15 μg/g) ( p < 0.05, n = 30, respectively). Pretreating the insects with phentolamine (0.1 μg/g) prevented the JBU- or octopamine-induced increase of grooming activity. JBU (6 μg/g) caused 65 ± 9% neuromuscular blockade in the cockroaches, an effect prevented by bicuculline (5 μg/g) ( p < 0.05, n = 6). JBU (6 μg/g) decreased the frequency whilst increasing the amplitude of the spontaneous neural compound action potentials (1425 ± 52.60 min −1, controls 1.102 ± 0.032 mV, p < 0.05, n = 6, respectively). Altogether the results indicate that JBU induces behavioral alterations in Nauphoeta cinerea cockroaches probably by interfering with the cholinergic neurotransmission. The neuromuscular blocking activity of JBU suggests an interplay between acetylcholine and GABA signaling. General significance: The search for novel natural molecules with insecticide potential has become a necessity more than an alternative. Understanding the mode of action of candidate molecules is a crucial step towards the development of new bioinsecticides. The present study focused on the neurotoxicity of Canavalia ensiformis urease, a natural insecticide, in cockroaches and revealed interferences on the cholinergic, octopaminergic and GABA-ergic pathways as part of its entomotoxic mode of action.